-12(b+8)=-12

Simple and best practice solution for -12(b+8)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12(b+8)=-12 equation:



-12(b+8)=-12
We move all terms to the left:
-12(b+8)-(-12)=0
We add all the numbers together, and all the variables
-12(b+8)+12=0
We multiply parentheses
-12b-96+12=0
We add all the numbers together, and all the variables
-12b-84=0
We move all terms containing b to the left, all other terms to the right
-12b=84
b=84/-12
b=-7

See similar equations:

| (x^2)+4x-12=0 | | 8w−10=10w | | 3(x-5-13=17 | | -9/5y=2/7 | | 16=2(5v–2) | | 2x+3x+2=2x+20 | | 12x-2(x+1)=2x+38 | | x/4+14=15 | | 7=m-5/2 | | x/3-12=-24 | | 4x−7=13 | | 3-2r=10 | | 13x+12=1112 | | 2(7n+2)=5(1+3n)-5 | | -8+x=6-x | | 5x-2(x-7)-6=14 | | 1/5x+1/5=-4/5x-4/5 | | 8y+2+2y+7=59 | | 2x+2x=-7+-3x | | 12x-47=15 | | 38=y/2+14 | | -4(x-2)-2x=24-2(x+2) | | -1+6v=7v-8-2v | | 1-x+5-10=-40 | | -3+5a=2a+12 | | x/3-4=71 | | 6y+9-y=29 | | 10x+-5x-x=16 | | -1-3x+10-6-1=0 | | 6a-3a-a=12 | | -9=x-8-x | | 8-16x+6=-1 |

Equations solver categories